Espinha bífida e mielodisplasia em ruminantes: Relato de caso - Borges, Alexandre Secorun [UNESP]; Mendes, L. C. N.; Vasconcelos, R.; Alves, Ana Liz Garcia [UNESP]; Rodrigues, Celso Antonio [UNESP] (My University, 1997)
Spina bifida with mielodysplasia are described in calf and lamb in this report. Locomotor abnormalities in the pelvic limbs and vertebral malformation were found in both animals, and arthrogryposis was also present in the calf. The mielodysplasia was very similar in these animals, and both were characterized by non separation of ventral and dorsal horns, areas with medular canal duplication and syringomyelia. No cases of spina bifida was previously described in Brazil.
Myelodysplasia and spina bifida in ruminants: A case report
Keywords: Arthrogryposis; Calf; Lamb; Myelodysplasia; Spina bifida; Syringomyelia